Open Data and the Future of Science - Boulton, Geoffrey (Septentrio Conference Series, 2014)
>> See video of presentation (54 min.) Open Science is not new, it was the bedrock on which the scientific revolutions of the 18th and 19th centuries were built. Its open publication of scientific concepts and the evidence (the data) on which they were based allowed scrutiny of the logic of an argument and replication of observations or experiments or their refutation. It has been the basis of so-called “scientific self-correction”. But the technological revolution of recent decades has produced an unprecedented explosion in the human capacity to acquire, store and manipulate data and information and to instantaneously communicate them globally, irrespective of location. It has produced fundamental changes in human, social and economic behaviour and has implications for research and learning that are far more profound and pervasive than those that followed Gutenberg’s invention of the printing press, including the way that science engages with the wider community. But the explosion of data is also undermining self-correction through the difficulty of making large volumes of supporting data concurrently available in a scrutinisable form, risking both the method of science and its credibility. This poses a major challenge for modern science to stimulate open release and sharing of data in ways that also facilitate new modes of collaboration and that increase creativity through interaction of many brains and many communities unbounded by institutional walls. We need to challenge and re-define many of the habits and norms of researchers and their institutions if the research community if it is to exploit technological opportunities, maintain self-correction and maximize the contribution of research to human understanding and welfare. Fortunately the response to these imperatives is growing, through the enunciation of principles for open science, the development of procedures and tools and the engagement of researchers, universities, funders, publishers, learned societies and governments.